Linguistic Politeness Analysis of Indonesia’s Prominent YouTube Influencers - Shalekhah, Rizmadina Amalia; Estayani, Septy Artika; Sari, Melinda; Nugroho, Raden Arief (Journal of English Language Teaching and Linguistics, 2020)
This paper aims to analyze the linguistic politeness of Indonesia's YouTube influencers. The findings show the type of YouTube content typology that has been found in this data according to Mediakix (2019) which gets a percentage of 40% is the type of interview content. This type of content is dominated by male Youtuber Meanwhile, according to Dynel (2015) theory, the category that gets the highest percentage in the category of insults with 43% of the total data. Based on a review of several studies, it was found that there are similarities and differences between one study and another. After analyzing the similarities and differences in previous studies, a novelty was found, namely in this study discussing the politeness patterns of YouTube influencers related to gender. Besides, this study analyzed 41 video sources which were used as research material. It can be seen that Indonesian Youtubers do not use polite language in order to trigger humour in its content. Interestingly, all humours made by these Youtubers contains politeness maxim deviation.